2010
DOI: 10.14741/ijcet/spl.2.2014.13
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Behavior of Al2O3 Filled Jute Fiber Reinforced Epoxy Composites

Abstract: Now -a-days

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…Figure (5) shows the true density for the specimens unsaturated polyester+3% carbon fiber + (0.5%, 1%, 1.5%, 2%) carbon nanotube, unsaturated polyester+3% glass fiber + (0.5%, 1%, 1.5%, 2%) carbon nanotube and unsaturated polyester +3% Kevlar fiber + (0.5%, 1%, 1.5%, 2%) carbon nanotube. From the figure (5) it may be noted in all values of the nano composites density increased with increasing the volume fraction due the more voids are found with the addition of fiber and filler in the nano composites material [24]. In figure (5) can be seen that the specimens UP+ 3%C.F+0.5%-2% CNTs, UP+3% GF+0.5%-2% CNTs,UP+ 3%K.F+0.5-2% CNTs) have density higher than specimen UP, This is due to the fact that these fibers have a high density compared with the density of UP, also can be observed that the higher density has been found for the specimen (UP+ 3% G.F + 2% CNTs) than other specimens at same volume fraction because these CNTs are made to diminish or fill the voids and spaces which were inside the UP matrix.…”
Section: True Densitymentioning
confidence: 94%
“…Figure (5) shows the true density for the specimens unsaturated polyester+3% carbon fiber + (0.5%, 1%, 1.5%, 2%) carbon nanotube, unsaturated polyester+3% glass fiber + (0.5%, 1%, 1.5%, 2%) carbon nanotube and unsaturated polyester +3% Kevlar fiber + (0.5%, 1%, 1.5%, 2%) carbon nanotube. From the figure (5) it may be noted in all values of the nano composites density increased with increasing the volume fraction due the more voids are found with the addition of fiber and filler in the nano composites material [24]. In figure (5) can be seen that the specimens UP+ 3%C.F+0.5%-2% CNTs, UP+3% GF+0.5%-2% CNTs,UP+ 3%K.F+0.5-2% CNTs) have density higher than specimen UP, This is due to the fact that these fibers have a high density compared with the density of UP, also can be observed that the higher density has been found for the specimen (UP+ 3% G.F + 2% CNTs) than other specimens at same volume fraction because these CNTs are made to diminish or fill the voids and spaces which were inside the UP matrix.…”
Section: True Densitymentioning
confidence: 94%
“…From the Tables it can be noticed that a pronounced effect of the addition of 3% glass fiber with 6% volume frication from (nano powder) percent on the erosion wear, also can be seen the specimen (Epoxy + 3% Glass Fiber +6% TiO 2 ) give better erosion resistance than the composites filled with (2% TiO 2 and 4% TiO 2 ) at 15 hour) time, (30 cm) stand-off distance, (60•) angle, (425μm) grin size of sand, (30 Ċ) temperature, (350 gm) salt content in (2 liter) water content. From the Tables (5), (6) and Figures (6) it is clear that there is a pronounced effect of the addition of 3% glass fiber with 6% volume frication from (micro powder) percent on the erosion wear, it can noticed the specimens (Epoxy +3% Glass Fiber + 6% TiO 2 ) give better erosion resistance than the composites filled with (2% TiO 2 and 4% TiO 2 ) at (15 hour) time, (30 cm) stand-off distance, (60•) angle, (425μm) grin size of sand, (30 Ċ) temperature, (350 gm) salt content in (2 liter) water content. Which may be related to its lower grain size with a good distribution and bonding.…”
Section: E Erosion Wear Testmentioning
confidence: 99%
“…Although the main process is the mechanical impact, caused by the impingement of solid particles on the target material, secondary processes, like thermal, chemical and physical reactions between the counterparts are taking place during erosion. Barkoula and Karger, (2002) have studied the influence of interfacial modification and relative fiber orientation (parallel, Pa and perpendicular, Pe) on the solid particle erosion has been investigated in unidirectional (UD) reinforced glass fiber (GF) epoxy (EP) composites. The interfacial modification is varied by (GF) sizing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jute and alumina as hybrid reinforcement in epoxy, they have concluded that hardness, strength, flexural and tensile modulus increased with increase in the fiber and filler loading. Alavudeen et al [19] have investigated the mechanical properties of woven banana fiber, kenaf fiber and banana/kenaf hybrid fiber composites. Mechanical properties such as tensile, flexural and impact strengths of woven banana/kenaf fiber hybrid composites increased due to the hybridization of kenaf with banana fibers.…”
mentioning
confidence: 99%